Epigenetic (re)programming of gene expression changes of CB1R and FAAH in the medial prefrontal cortex in response to early life and adolescence stress exposure - Demaili, Arijana; Portugalov, Anna; Dudai, Michal; Maroun, Mouna; Akirav, Irit; Braun, Katharina; Bock, Jörg (Frontiers in Cellular Neuroscience, 2023)
Environmental factors, including stress, that are experienced during early life (ELS) or adolescence are potential risk factors for the development of behavioral and mental disorders later in life. The endocannabinoid system plays a major role in the regulation of stress responses and emotional behavior, thereby acting as a mediator of stress vulnerability and resilience. Among the critical factors, which determine the magnitude and direction of long-term consequences of stress exposure is age, i.e. the maturity of brain circuits during stress exposure. Thus, the present study addressed the hypotheses that ELS and adolescent stress differentially affect the expression of regulatory elements of the endocannabinoid system, cannabinoid receptor 1 (CB1R) and fatty acid amide hydrolase (FAAH) in the medial prefrontal cortex (mPFC) of adult female rats. We also tested the hypothesis that the proposed gene expression changes are epigenetically modulated via altered DNA-methylation. The specific aims were to investigate if (i) ELS and adolescent stress as single stressors induce changes in CB1R and FAAH expression (ii) ELS exposure influences the effect of adolescent stress on CB1R and FAAH expression, and (iii) if the proposed gene expression changes are paralleled by changes of DNA methylation. The following experimental groups were investigated: (1) non-stressed controls (CON), (2) ELS exposure (ELS), (3) adolescent stress exposure (forced swimming; FS), (4) ELS + FS exposure. We found an up-regulation of CB1R expression in both single-stressor groups and a reduction back to control levels in the ELS+FS group. An up-regulation of FAAH expression was found only in the FS group. The data indicate that ELS, i.e. stress during a very immature stage of brain development, exerts a buffering programming effect on gene expression changes induced by adolescent stress. The detected gene expression changes were accompanied by altered DNA methylation patterns in the promoter region of these genes, specifically, a negative correlation of mean CB1R DNA methylation with gene expression was found. Our results also indicate that ELS induces a long-term “(re)programming” effect, characterized by CpG-site specific changes within the promoter regions of the two genes that influence gene expression changes in response to FS at adolescence.